ECOPRENEURSHIP FOR SUSTAINABILITY BUSINESS IN MILLENNIAL GENERATION - Christina, Lenny; Young, Felina; Siswanti, Indra (Jurnal Riset Bisnis dan Manajemen, 2024)
This study aims to analyze the influence Ecopreneurship implications on Competitive Advantage and sustainability business SMEs millennia generation in Indonesia and Philippine. This research done with Quantitative Method using Structural Equation Modelling (SEM) analysis with software Partial Least Square (PLS). The population in this study was a sample of 100 people and the sampling technique is random sampling. This study proves the effect of ecopreneurship on competitive advantage and business sustainability except that eco-opportunity does not affect business sustainability. It is also proven that competitive advantage does not mediate Eco-commitment to Business Sustainability in the millennial generation. The novelty in this research is the Sustainability Business model for the millennial generation through ecopreneurship.